2020
DOI: 10.1186/s12888-020-02902-8
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of The Opening Minds Stigma Scale for Health Care Providers and psychometric properties of its Hungarian version

Abstract: Background The Opening Minds Stigma Scale for Health Care Providers (OMS-HC) is a widely used questionnaire to measure the stigmatising attitudes of healthcare providers towards patients with mental health problems. The psychometric properties of the scale; however, have never been investigated in Hungary. We aimed to thoroughly explore the factor structure of the OMS-HC and examine the key psychometric properties of the Hungarian version. Methods The OMS-HC is a self-report questionnaire that measures the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…Other criteria, such as eigenvalue larger than 1 or significance of the Chi-square difference test, suggested more than four factors, but such a large number of factors was inconsistent with the conception of the scale and the existing literature. A study in Hungary [ 43 ] found three factors, which is not entirely inconsistent with our findings ( Table 2 ), but four factors is meaningfully more than was reported in the original OMS-HC development paper, where two factors were found using 12 items. Our three-factor solution showed several cross-loadings, and the factors did not yield a clear interpretation.…”
Section: Resultscontrasting
confidence: 88%
“…Other criteria, such as eigenvalue larger than 1 or significance of the Chi-square difference test, suggested more than four factors, but such a large number of factors was inconsistent with the conception of the scale and the existing literature. A study in Hungary [ 43 ] found three factors, which is not entirely inconsistent with our findings ( Table 2 ), but four factors is meaningfully more than was reported in the original OMS-HC development paper, where two factors were found using 12 items. Our three-factor solution showed several cross-loadings, and the factors did not yield a clear interpretation.…”
Section: Resultscontrasting
confidence: 88%
“…The con rmatory factor analysis showed good model t with respect of the original version. This is in line with a recent OMS-HC validation study in Chile and partly consistent with a Hungarian study that ran a series of factor analyses, resulting in a nal two-factor solution [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…The German study showed good internal consistency for the total scale (α = 0.74) and lower for the three factors (α < 0.70), and the authors maintained the original factor structure ( Zuaboni et al, 2021 ). The Hungarian study ( Őri et al, 2020 ) also had good internal consistency (α = 0.73) and lower internal consistency for the three factors of the factor structure (α < 0.70). However, its results showed that one of its items should be removed ( Őri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…The Hungarian study ( Őri et al, 2020 ) also had good internal consistency (α = 0.73) and lower internal consistency for the three factors of the factor structure (α < 0.70). However, its results showed that one of its items should be removed ( Őri et al, 2020 ). In addition, although they obtained good results for a three-factor structure, their results indicated good results for a bifactor structure with one global factor and three specific factors ( Őri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation